PREVALENCE OF ANATOMICAL VARIATION OF THE SIXTH CERVICAL VERTEBRA AND ASSOCIATION WITH VERTEBRAL CANAL STENOSIS AND ARTICULAR PROCESS OSTEOARTHRITIS IN THE HORSE. Issue 3 (25th February 2016) - DeRouen, Anthony; Spriet, Mathieu; Aleman, Monica
Abstract : The sixth cervical vertebra (C6) has unique morphology due to a ventral extension from the transverse process known as the ventral lamina. Little information was found regarding the prevalence and clinical relevance of morphologic variations. Aims of this observational, retrospective study were to characterize C6 morphologic variations in a large sample of horses. Cervical radiographic studies of 100 horses were retrieved. Data recorded were signalment, clinical history, morphology of the C6 ventral lamina, presence of articular process osteoarthritis, and presence of static vertebral canal stenosis. Morphologic variations were found in C6 vertebrae for 24/100 horses, with symmetric absence of the ventral lamina in nine horses and asymmetric absence in 15. Anomalous C6 vertebrae were more common in Warmbloods, with 19/55 Warmbloods in the population being affected ( P = 0.006). No association was found with sex. There was no significant difference in the mean of the intravertebral sagittal ratios between horses with normal or anomalous C6 vertebrae; however there was a significantly greater proportion of horses with anomalous C6 vertebrae that had an intravertebral sagittal ratio of less than 0.5 at C6 ( P = 0.047). There was no association between the morphology of C6 and articular process osteoarthritis. Anomalous C6 vertebrae in our population were associated with a higher likelihood of cervical pain ( P = 0.013). Authors propose that morphologic variations in the C6 ventral laminae could be linked to other developmental abnormalities such as vertebral canal stenosis, might affect regional biomechanics and should therefore be considered clinically relevant in horses. Future, controlled prospective studies are needed to test this theory.